Comparative Analysis of Bioactive Phytochemical Profiles of Moringa Oleifera and Aegle Marmelos Grown in Bundelkhand - Shahina Kalim; Manish Kumar; Vivek Mishra (Emerging Trends in Metabolites, 2024)
A comparative analysis of the bioactive phytochemical profiles of Moringa oleifera and Aegle marmelos grown in the Bundelkhand region was conducted to explore their potential health benefits. These properties make healing plants valuable in herbal medicine, supporting various aspects of health and well-being. The study aimed to determine the differences in the concentrations of bioactive compounds such as phenolic, flavonoids, alkaloids, and vitamins C and E in the leaves and fruits of these plants. M. oleifera exhibited higher concentrations of phenolics and flavonoids compared to A. marmelos, indicating stronger antioxidant and anti-inflammatory properties. Aegle marmelos showed higher levels of alkaloids, which are known for their antimicrobial and anti-cancer activities. Interestingly, both plants exhibited comparable levels of vitamins C and E, suggesting similar potential for boosting immune function and reducing oxidative stress. This comparative study was conducted by M. oleifira and A. marmelos grown in Bundelkhand, highlighting their potential as sources of natural remedies and functional foods for promoting health and preventing diseases. The research investigates the phytochemical content of M. oleifera and A. marmelos from the Bundelkhand region, identifying bioactive compounds that may possess medicinal benefits, validating their traditional therapeutic applications. This study evaluates the phytochemical properties of M. oleifera and A. marmelos from the Bundelkhand region. The investigation revealed a large number of bioactive chemicals. It emphasises the potential of such chemicals as natural antioxidants and healing agents.
Keywords: Aegle Marmelos; Bioactive Phytochemicals; Bundelkhand Region (India); Moringa Oleifera; Phytochemical Profiles